A climate responsive approach for thermal comfort in Malaysian buildings / Zainalazlan Md Zain - Md Zain, Zainalazlan (2006)
Climate has been recognized as one the major factors which influences energy consumption in buildings. Malaysia is a hot and humid country and the climate of Malaysia imposes thermal pressure on buildings due to thermal difference between the desired internal temperature and extremes of the external temperature. The building envelop is to protect from the extreme temperature while the optimum set point for air conditioning system will avoid energy wastage. Adaptive thermal comfort model shows that human thermal comfort is dependent on the average external ambient temperature, thus the monthly average temperature is required for determining the thermal comfort set point temperature. Managing and controlling the heat from the ambient external condition to the thermally comfortable internal condition requires knowledge on the external climate condition, the desired internal thermal comfort condition and the interfacing building envelope behavior. This thesis which analyses the various external climate parameters for seven typical locations in Malaysia, uses adaptive thermal comfort model to recommend optimum design temperature as guideline, either for air conditioning control parameters or natural ventilation. The temperature design guideline is classified into maximum preferred thermal comfort, thermal comfort and acceptable thermal comfort. Psychrometric analysis is a very useful tool, developed in this thesis using Visual Basic for analyzing the climate with reference to the thermal comfort zone. It gives the moist air properties extra information, such as enthalpy and humidity ratio, which are very relevant to when estimating the amount of heat and water that is needed to be extracted for thermal comfort in buildings. Design tools were also developed to simulate the influence of solar radiation on building envelope under transient dynamic condition. These design tools are very significant in facilitating the understanding of thermal behavior and proper design condition for energy efficiency and thermal comfort.